2016
DOI: 10.1099/mic.0.000176
|View full text |Cite
|
Sign up to set email alerts
|

Cannibalism stress response in Bacillus subtilis

Abstract: When faced with carbon source limitation, the Gram-positive soil organism Bacillus subtilis initiates a survival strategy called sporulation, which leads to the formation of highly resistant endospores that allow B. subtilis to survive even long periods of starvation. In order to avoid commitment to this energy-demanding and irreversible process, B. subtilis employs another strategy called 'cannibalism' to delay sporulation as long as possible. Cannibalism involves the production and secretion of two cannibali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…This is particularly clear for endospore-formation, a notably energy-demanding process (Höfler et al, 2016) that leads to the formation of a resistance structure. EFF have been used as models to investigate the cost of relative simple phenotypes (e.g., maintenance of simple biosynthetic pathways; Maughan et al, 2007), as well as more complex ones, such as spore development (Callahan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly clear for endospore-formation, a notably energy-demanding process (Höfler et al, 2016) that leads to the formation of a resistance structure. EFF have been used as models to investigate the cost of relative simple phenotypes (e.g., maintenance of simple biosynthetic pathways; Maughan et al, 2007), as well as more complex ones, such as spore development (Callahan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the depletion of the measured overflow metabolites at the end of cultivation, an OTR of 6 mmol·L −1 ·h −1 is measurable ( Figure 3a). The respiratory activity indicates the consumption of undetected overflow metabolites, storage compounds or of nutrients deriving from lysed cells (Gebhard et al, 2016;Gonzalez-Pastor, 2003). In summary, glucose starvation causes completely undefined conditions in terms of nutrient availability.…”
Section: Batch Cultivationmentioning
confidence: 99%
“…In a recent report, it was demonstrated that the Bce and Psd system strongly respond to both cannibalism toxins (Höfler et al 2016). In liquid cultures, SKF seems to be the predominant stimulus, but SDP also contributes to the overall response (Höfler et al 2016). Likewise, the Lia system seems to be induced by yet another poorly characterized AMP encoded by the yydF gene (Butcher et al 2007).…”
Section: Extrinsic Amp Challenge Versus Intrinsic Amp Productionmentioning
confidence: 94%
“…Their death releases nutrients that allow the cannibal subpopulation to overcome temporary phases of starvation without the need to sporulate (Gonzalez-Pastor 2011). In a recent report, it was demonstrated that the Bce and Psd system strongly respond to both cannibalism toxins (Höfler et al 2016). In liquid cultures, SKF seems to be the predominant stimulus, but SDP also contributes to the overall response (Höfler et al 2016).…”
Section: Extrinsic Amp Challenge Versus Intrinsic Amp Productionmentioning
confidence: 98%